Wilson Barstow papers - Barstow, Wilson, -1869.
Letters written by Barstow from Baltimore, Md., Fort Monroe, Va., and New York, N.Y., chiefly to his sister, Elizabeth Stoddard, relating to his activities during the Civil War.
Army officer and aide to General John A. Dix.
Collection material in English.
Keywords: Stoddard, Elizabeth, -- 1823-1902 -- Correspondence; Baltimore (Md.) -- History -- Civil War, 1861-1865.; Fort Monroe (Va.) -- History -- Civil War, 1861-1865.; Maryland -- History -- Civil War, 1861-1865.; New York (N.Y.) -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Personal narratives; Virginia -- History -- Civil War, 1861-1865.; Army officers